Monostotic Fibrous Dysplasia with Rare Histopathologic Features: A Case Report - Abbas Karimi; Mahboube Hasheminasab; Samira Derakhshan; Dariyoush Goudarzi Pour; Mahdis Khazaeli Najafabadi; Razie Hosseininavaz (Iranian Journal of Medical Sciences)
Fibrous dysplasia is a slow-progressing benign condition characterized by abnormal bone formation that leads to some skeletal disorders. Although some of the fibrous dysplasia have unusual clinical and radiographic features that can lead to a challenging diagnosis, most lesions reveal an expansile bone defect due to cortex thinning. This report presented a case of monostotic fibrous dysplasia of a 43-year-old woman with involvement of the right maxillary jaw and sinuses, which indicated unusual histopathological features. The patient was referred to the Department of Oral and Maxillofacial Surgery of Tehran University of Medical Sciences (Tehran, Iran) in 2022. Radiological and histological findings were discussed. The unusual histomorphic pattern of the lesion caused uncertainty and resulted in a missed definitive diagnosis in the primary biopsy. It was highlighted that awareness of rare histologic variants in fibro-osseous lesions especially fibrous dysplasia was required to improve diagnostic confidence.